The perfect "potty" zoo : the funniest abc book - Green, Agnes ([United States?] : April Tale Books, 2017)
"Animals from a to z are very much like you, they play, they eat, they sleep, they dream, they even pee and poo!" -- cover
Target audience:2-3 years
Keywords: Toilet training -- Juvenile literature; Picture books